Executable task force rheumatology diseases. Diagnosis and management approaches - Vizir, V. A.; Berezin, A. E.; Pysanko, O. V.; Візір, Вадим Анатолійович; Березін, Олександр Євгенійович; Писанко, Оксана Володимирiвна (Zaporozhye state medical university, 2017)
Executable task force is addressed to students of 5th and 6th courses of medical university for helping to study of internal medicine according rheumatology